Modified Mustardé-type cervicofacial flap for reconstruction of a zygomatic–maxillary defect secondary to squamous cell carcinoma: a case report - Camargo, Daniella A. P. L.; Cacique, Mauricio D.; Gutiérrez, Manuel M.; Trejo, Octavio D.; Rodríguez, Raúl S. C. (International Surgery Journal, 2025)
Cutaneous squamous cell carcinoma (cSCC) is one of the most frequent malignant skin neoplasms and represents a therapeutic challenge in anatomically exposed regions. It is characterized by its invasive and metastatic potential, with predilection for the head and neck, particularly in elderly men with chronic sun exposure. In Mexico, it ranks second among skin cancers in prevalence. A 93-year-old male patient presented with a squamous cell carcinoma located in the right maxillary region. Complete oncologic resection with tumor-free margins was performed, followed by reconstruction using a cervicofacial rotation flap of the Mustardé type and lymph node dissection at levels IB and IIA. The postoperative course was favorable, with no local or systemic complications. At follow-up, the flap showed good perfusion and a well-healed aesthetic scar, with preserved facial symmetry and no signs of necrosis or lower eyelid retraction. The Mustardé-type cervicofacial flap provides a safe and versatile option for the reconstruction of extensive oncologic facial defects. Its wide arc of rotation, reliable vascular supply, and excellent color and texture match allow for satisfactory functional and cosmetic results. In this case, deep anchorage to the malar periosteum and zygomaticus central fascia provided stability and reduced traction on the lower eyelid. The Mustardé-type cervicofacial flap remains an effective reconstructive option for significant facial skin defects secondary to oncologic resections, achieving favorable functional and aesthetic outcomes, particularly in elderly patients.